The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su15010606
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Autonomous Use of Technology for Language Learning for EFL University Students of Different Proficiency Levels

Abstract: Different aspects of second-language learners’ autonomous use of technology for language learning have been investigated and its positive effects on language learning have been reported. However, there is a paucity of research on whether language learners’ different proficiency levels are associated with their perceptions of their own autonomous use of technology-enhanced language learning (TELL). Therefore, this study examines the autonomous use of TELL outside the English classes of English learners of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 64 publications
0
11
0
1
Order By: Relevance
“…Introducing the learners to an advanced vocabulary tool beyond a dictionary (the corpus Digitales Wörterbuch der deutschen Sprache , DWDS) provides them with concrete language in context and opportunities for potential incidental learning. The practice of using the corpus tool could potentially encourage self‐sustained learning (Xiao & Chen, 2018) and contribute to learner autonomy (e.g., Li‐Tang, 2023; Little et al., 2017; Lenkaitis, 2020; Teng, 2019; Trang, 2022).…”
Section: Pedagogical Approaches and Rationalementioning
confidence: 99%
“…Introducing the learners to an advanced vocabulary tool beyond a dictionary (the corpus Digitales Wörterbuch der deutschen Sprache , DWDS) provides them with concrete language in context and opportunities for potential incidental learning. The practice of using the corpus tool could potentially encourage self‐sustained learning (Xiao & Chen, 2018) and contribute to learner autonomy (e.g., Li‐Tang, 2023; Little et al., 2017; Lenkaitis, 2020; Teng, 2019; Trang, 2022).…”
Section: Pedagogical Approaches and Rationalementioning
confidence: 99%
“…Media use for socialization purposes is characterized by an increased attention to language to achieve effective communication and a greater focus on accurate language use (Lai et al, 2018;Yu, 2023), suggesting a potential positive contribution of this type of activities to vocabulary development. However, research evidence on the effect of social media use on vocabulary development is rather mixed (Alharthi, Bown & Pullen, 2020).…”
Section: Purposes Of Informal Digital Activities and Vocabulary Devel...mentioning
confidence: 99%
“…The language learners may customise their language learning experience based on their own strengths and limitations and get the best outcomes by employing technology tools. With rich online resources, technology provides students a plethora of options for autonomous learning (Yu, 2022). Numerous studies have shown that encouraging student autonomy in the classroom is crucial (Cheng, 2019;Melvina & Suherdi, 2019).…”
Section: Good Language Learnersmentioning
confidence: 99%